Evaluating the comprehensive impacts of tourism in Hainan by intergrating input-output model with MCDM methods - Lin, Ping-Ping; Li, Deng-Feng; Jiang, Bin-Qian; Yu, Gao-Feng; Wei, An-Peng (Technological and Economic Development of Economy, 2020)
To evaluate the comprehensive impacts of tourism in Hainan, this paper proposes an approach integrating input-output (IO) model with multi-criteria decision making (MCDM) methods. Four steps are taken: (1) constructing an extended IO model that can separate out domestic and imported effects from the traditional IO system; (2) constituting a 3-level evaluation criteria hierarchy based on various tourism multipliers obtained from the extended IO model; (3) calculating the weights of criteria using the entropy theory; (4) giving an evaluation of comprehensive impacts of tourism based on four MCDM methods – WSM, TOPSIS, ELECTRE, and PROMETHEE. Using Hainan 2002, 2007, and 2012 IO tables as database, the proposed approach is implemented in the empirical study of Hainan. The results show economic dimension is the most important consideration and the overall performance of tourism in Hainan shows a trend of first increasing and then decreasing from 2002 to 2012. Two types sensitivity analysis of weights show single criterion weight change has little influence on the results. But it is different when four dimensions weights change. Especially, when the environmental dimension is valued, the overall performance gets worse annually. These findings can offer insightful policies for the development of Hainan’s tourism.First published online 23 June 2020